The Effect of Red Algae (Eucheuma cottonii) Nanoemulgel on Cytokine Il-1 Beta Expression for Traumatic Ulcers Healing - Feranisa, Anggun; Nurhapsari, Arlina; Indriastanti, Rikha; Amalina, Rizki (Universitas Muhammadiyah Yogyakarta, 2024)
Red algae (Eucheuma cottonii) is a type of seaweed (Rhodophyceae). Eucheuma cottonii contains flavonoids and florotanin as an anti-inflammatory agent. The extracted red algae were formulated into nanoemulgel. This study aimed to determine the effect of red algae nanoemulgel (Eucheuma cottonii) in the expression of IL-1β cytokines on the healing of traumatic ulcers. The researcher applied true experimental research with a post-test-only control group design. This research was conducted by giving Eucheuma cottonii nanoemulgel concentrations of 20%, 35%, 50%, positive control, and negative control at the labial once a day, followed by evaluation using the IHC method. The results revealed that Eucheuma cottonii nanoemulgel extract affected the expression of IL-1β cytokines in healing traumatic ulcers by decreasing the amount of IL-1β cytokine expression. The results obtained a p-value of 0.05, which indicates a significant difference in the expression of the number of IL-1β cytokines in traumatic ulcers. This study concluded that the 20% Eucheuma cottonii extract nanoemulgel treatment group affected the amount of IL-1β by decreasing the expression of IL-1β cytokines. Nanoemulgel of 20% Eucheuma cottonii extract is considered effective as an anti-inflammatory material for traumatic ulcer healing.